2015
DOI: 10.1073/pnas.1518894112
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-1 receptor mediates cocaine-induced transcriptional regulation by recruiting chromatin-remodeling factors at the nuclear envelope

Abstract: The sigma-1 receptor (Sig-1R) chaperone at the endoplasmic reticulum (ER) plays important roles in cellular regulation. Here we found a new function of Sig-1R, in that it translocates from the ER to the nuclear envelope (NE) to recruit chromatin-remodeling molecules and regulate the gene transcription thereof. Sig-1Rs mainly reside at the ER-mitochondrion interface. However, on stimulation by agonists such as cocaine, Sig-1Rs translocate from ER to the NE, where Sig-1Rs bind NE protein emerin and recruit chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 58 publications
8
121
1
Order By: Relevance
“…As HDAC3 has been shown to bind the nuclear envelope protein emerin in muscle progenitors (Demmerle et al, 2013) and HDAC1‐3 have been shown to bind emerin and BAF in neuroblastoma cells (Tsai et al, 2015), we cannot rule out the possibility that tissue‐specific interactions of nuclear envelope proteins with diverse epigenetic enzymes might occur (Batrakou, Las Heras, Czapiewski, Mouras, & Schirmer, 2015; Worman & Schirmer, 2015). Along this line, mutations causing EDMD2 do not impair lamin A/C‐HDAC2 interaction (this study), while defects in emerin‐HDAC3 binding have been reported in EDMD1 (Collins, Ellis, & Holaska, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As HDAC3 has been shown to bind the nuclear envelope protein emerin in muscle progenitors (Demmerle et al, 2013) and HDAC1‐3 have been shown to bind emerin and BAF in neuroblastoma cells (Tsai et al, 2015), we cannot rule out the possibility that tissue‐specific interactions of nuclear envelope proteins with diverse epigenetic enzymes might occur (Batrakou, Las Heras, Czapiewski, Mouras, & Schirmer, 2015; Worman & Schirmer, 2015). Along this line, mutations causing EDMD2 do not impair lamin A/C‐HDAC2 interaction (this study), while defects in emerin‐HDAC3 binding have been reported in EDMD1 (Collins, Ellis, & Holaska, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HDAC2 has been shown to suppress p21 expression in human hepatocellular carcinoma via its binding to an Sp1‐binding site (Noh et al, 2011). On the other hand, it has been demonstrated that lamin A/C establishes direct interactions with histone deacetylases including SIRT1 (Cenni et al, 2014; Liu et al, 2012), SIRT6 (Ghosh, Liu, Wang, Hao, & Zhou, 2015), and HDAC1 (Kubben et al, 2016), while lamin partners at the nuclear envelope such as emerin, BAF, and LAP2beta interact with HDAC3 (Demmerle, Koch, & Holaska, 2013) or HDAC2 (Tsai et al, 2015). Moreover, lamin A/C has been demonstrated to bind gene promoters or neighboring domains and this binding has been linked to distinct transcriptional outcomes (Lee, Welton, Smith, & Kennedy, 2009; Lund & Collas, 2013; Mattout et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the S1R membrane topology makes it difficult to rationalize how the receptor could interact with proteins both in the cytoplasm and in the ER lumen. Interactions with several proteins or regions of protein that are found exclusively in the cytoplasm or the nucleus, including the C-terminus of the GluR1 subunit of the ionotropic glutamate receptor [57], STIM1 [58], and emerin [12], are consistent with S1R being a Type I membrane protein with a cytosolic C-terminus. However, an interaction at the C-terminus of S1R with BiP has been shown in cell extracts [2] and in vitro [25].…”
Section: Structural Implications For Membrane Topologymentioning
confidence: 83%
“…The Sig-1R is also found to translocate to the envelope of the nucleus [14, 15], where the Sig-1R interacts with a nuclear envelope-resident protein emerin and recruits therein a series of chromatin-remodeling factors to regulate the gene transcription [15]. Recently, many studies via experimental or bioinformatics means have identified or proposed the interaction of the Sig-1R with many other functional proteins in the plasma membrane, ER, mitochondria, and even the cytosol.…”
Section: The Sigma-1 Receptor: Brief History and Current Statusmentioning
confidence: 99%